Unity Snappable Meshes - Fachada, Nuno (2022)
The Snappable Meshes algorithm procedurally generates 3D maps for computer games by iteratively selecting and linking pre-built map pieces via designer-specified connectors. In this paper we present an implementation of this algorithm in the Unity game engine, describing its architecture and discussing core implementational solutions. A number of examples illustrate the potential of the algorithm and the capabilities of the software. We assess the application’s impact on past and ongoing research, and how it can be improved to support future research questions. Keywords: Procedural content generation (PCG) ; Computer games ; Layout ; Designer-centric methods ;3D maps ; Unity game engine